Edukasi Dan Inovasi Untuk Masa Depan Yang Lebih Cerah - Rosalia, Ananda Riza; Arifa, Diah Anindya; Arryanto, Bimamrulloh Dhimas; Fajri, Wildan; Khomeini, Khomeini; Rachman, Renandri Abdillah; Asih, Trinia Sefti; Kholik, Fikri Abdul; Latif, Muhammad Ghafar; Akmalia, Lila Maisya; Alifi, Fasyandira Gresila Sekar; Suryanto, Suryanto (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
This program is a form of community service aimed at developing the community's potential and improving its welfare. The community service program is located in Dusun Suropati, Hargotirto Village, Kokap District, Kulon Progo Regency, Special Region of Yogyakarta. It focuses on three main programs: Dusun Bersinar (Drug-Free Hamlet), Pasar Online Kampung (Village Online Market), and Bincang Parenting dan Stunting (Parenting and Stunting Discussion). This program aims to create a healthy, safe, and productive environment. The Dusun Bersinar (Drug-Free Hamlet) program seeks to enhance public knowledge about the dangers of drugs, their health impacts, and legal consequences. This activity is carried out through public education and counseling under the theme "Living Without Drugs, Living More Meaningfully," involving health workers, the community, and the younger generation. The Pasar Online Kampung (Village Online Market) program supports MSMEs in expanding their market reach and equipping business actors with the skills to compete in the digital marketplace. This activity includes training small business owners on how to use social media for digital marketing. Meanwhile, the Bincang Parenting dan Stunting (Parenting and Stunting Discussion) program aims to raise awareness of the importance of balanced nutrition in preventing stunting and the significance of proper parenting for children's development. This program involves health workers, posyandu (integrated health service post) cadres, and mothers in interactive discussions to enhance understanding and awareness of the family's role in supporting optimal child growth. Combining these three programs is expected to significantly impact the community. A drug-free hamlet will create a safer and more conducive environment, market digitalization will improve the community’s economic well-being, and increased parenting awareness will result in a healthier and more intelligent generation. With collaboration between students and the community, this community service program is expected to be an innovative solution for developing a progressive, healthy, and prosperous village in a sustainable manner